Student Empowerment Management In Improving The Graduate's Quality (Multi-Site Study In MAN 1 Lamongan And MA MA’Arif 7 Sunan Drajat Lamongan) - Furqon, M.; Akhyak, Akhyak; Aziz, Abd.; Harris, Syahzanan (CV. Inara, 2024)
The background to this research is the results of the researcher's observations regarding the management conditions for student empowerment at MAN 1 Lamongan and MA MA'Arif 7 Sunan Drajat in improving the quality of graduates. This research focuses on student empowerment needs to improve graduate quality at MAN 1 Lamongan and MA MA'Arif 7 Sunan Drajat Lamongan. This research uses the Natural (Naturalistic Paradigm) approach. Therefore, this research uses a qualitative approach with a multisite study. The research results regarding the need for student empowerment in improving the quality of graduates at MAN 1 Lamongan refer to five student needs. First, It needs to get to know blended learning, research classes, Olympic classes, credit classes, and prodistics classes. Second, there are potential tests, academic potential tests, Al-Qur'an reading and writing tests, and student psychological tests. Third, student arrangements at MAN 1 Lamongan follow government policy, and the curriculum follows IKM, while quality uses ISO. Fourth, the number of students accepted or determining the number of students accepted. Fifth, there are programs for student activities based on the school's vision and mission. The student empowerment needs to improve the quality of graduates in MA. MA'Arif 7 Sunan Drajat refers to 7 needs of students, namely fatwa from Kyai, KTSP curriculum, superior majors, supporting needs (skills), Blended Learning, number of students accepted, and preparation of student activity programs are also needed.